Unmet needs of Italian physicians managing patients with inflammatory bowel disease. Issue 2 (February 2019) - Bezzio, Cristina; Imperatore, Nicola; Armuzzi, Alessandro; Rizzello, Fernando; Manes, Gianpiero; Bossa, Fabrizio; Calabrese, Emma; Caprioli, Flavio; Daperno, Marco; Mocciaro, Filippo; Orlando, Ambrogio; Papi, Claudio; et al.
Abstract: Background: Little is known about the unmet needs of physicians caring for patients with inflammatory bowel disease (IBD). Aims: This study explored the practical difficulties and needs for professional updating of Italian IBD physicians. Methods: A questionnaire was distributed to 600 physicians attending IG-IBD meetings. Results: 280 physicians completed the questionnaire (46.7%). On a 5-point Likert scale (from 1, strongly disagree to 5, strongly agree), they identified the most problematic issues in managing IBD patients as increasing bureaucracy (3.9), lack of extra-gastroenterological IBD expertise (3.4), lack of diagnostic techniques (3.1) and budget limitations (2.9). The most lacking techniques, ranked from 1 (greatest need) to 9 (lowest need), were: anti-drug antibody and trough level assays (2.7), device-assisted enteroscopy (3.1), exploration under anaesthesia (3.2), MR enterography (3.2), and bowel ultrasonography (3.3). About professional updating, respondents indicated (on a 5-point Likert scale) that helpful topics were practical medicine (4.3), managing difficult patients (4.1), and guidelines (4.0). The most desired modality for updating was residential courses on clinical practice (4.3). Conclusion: Several factors potentially limit the best management of IBD patients in Italy. Satisfying these unmet needs could improve care for IBD patients.